EFFECTS OF RICIAN FADING ON THE OPERATION OF AERONAUTICAL SATELLITE OFDM CHANNEL - Kharchenko, Volodymyr; Grekhov, Andrii; Ali, Ismail; Udod, Yulia (Proceedings of National Aviation University (archive), 2016)
The aim of this study is to investigate the influence of Rician fading on messages transmission via the aeronautical satellite OFDM channel with adaptive modulation and the development of a method for estimating the parameters of such a channel. Methods: To study the effect of Rician fading on messages transmission via aeronautical satellite OFDM channel with adaptive modulation the original model of the communication channel “Aircraft-Satellite-Ground Station” was built using software package MATLAB Sіmulіnk. The model includes “Aircraft Transmitter”, “Uplink/Downlink Path”, “Satellite Transponder”, and “Ground Station Receiver”. Each modulator block in the modulation bank performs convolutional coding and puncturing using code rates of ½, ²/3, and ¾, data interleaving, BPSK, QPSK, 16-QAM, and 64-QAM modulation. Results: Dependences of Estimated channel SNR on the ratio between the power of the LOS component and the diffuse component, on the downlink gain and delay in the diffuse component for different Doppler spectrum types and Doppler frequency offsets were obtained. A method for estimating the parameters of the satellite channels with fading was proposed. Discussion: The realistic model of aeronautical satellite OFDM link with Rician fading is developed for the first time on a basis of IEEE 802.11a standard and used for channel parameters evaluation. Proposed in this article approach can be considered as a method for estimating parameters of the channel with fading.